SCHEMA-ACTIVATED MULTIMEDIA INSTRUCTION AND ITS EFFECT ON EFL STUDENTS’ CRITICAL LISTENING SKILLS - Dwi Rara Saraswaty; Hadiyanto; Eddy Haryanto (University of Kuningan, 2026)
Abstract Critical listening is an essential higher-order academic skill for EFL learners, particularly in higher education contexts where students are required to engage with complex spoken discourse such as academic discussions. However, listening instruction often emphasizes surface-level comprehension rather than evaluative and interpretive processing. Grounded in schema theory, multimedia learning theory, and metacognitive listening theory, this study investigates the effect of schema-activated multimedia instruction on EFL students’ critical listening performance in academic discussion contexts. Employing a quantitative quasi-experimental design, the study involved two intact classes of undergraduate EFL students. The experimental group received instruction integrating prior knowledge activation and multimedia support within a metacognitive listening sequence, while the control group received conventional listening instruction. Data were collected through pre-test and post-test measures of critical listening performance and analyzed using descriptive and inferential statistics. The results reveal that students exposed to schema-activated multimedia instruction demonstrated significantly higher critical listening performance than those in the control group. The findings indicate that critical listening can be systematically developed through instructional design that integrates cognitive and pedagogical principles, contributing empirical evidence to EFL listening pedagogy in higher education contexts.